2007
DOI: 10.1103/physrevd.76.083009
|View full text |Cite
|
Sign up to set email alerts
|

High-energy cosmic rays and neutrinos from semirelativistic hypernovae

Abstract: The origin of the ultrahigh-energy (UHE) cosmic rays (CRs) from the second knee (∼ 6 × 10 17 eV) above in the CR spectrum is still unknown. Recently, there has been growing evidence that a peculiar type of supernovae, called hypernovae, are associated with sub-energetic gamma-ray bursts (GRBs), such as SN1998bw/GRB980425 and SN2003lw/GRB031203. Such hypernovae appear to have high (up to mildly relativistic) velocity ejecta, which may be linked to the sub-energetic GRBs. Assuming a continuous distribution of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
148
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(154 citation statements)
references
References 63 publications
(59 reference statements)
2
148
0
4
Order By: Relevance
“…Thanks to their high gas densities, f pp can be quite high and the observed neutrino flux level can be well explained as long as CRs can be accelerated above 100 PeV energies [28,29,23,14,30]. However, ordinary supernova remnants are not able to accelerate CRs up to this energy, so a lot of speculations have recently been made, including supermassive black hole activities [14], galaxy mergers [31], super bubbles, interaction-powered supernovae [32], hypernovae [33,34,23,35], transrelativistic supernovae and GRBs [36,37,38,39,40]. But it is highly unclear whether different populations lead to a smooth power-law spectrum and why the energy budget of rare transients is almost comparable to that of ordinary supernovae [23].…”
Section: Extragalactic Astrophysical Sources Hadronuclear Production mentioning
confidence: 99%
“…Thanks to their high gas densities, f pp can be quite high and the observed neutrino flux level can be well explained as long as CRs can be accelerated above 100 PeV energies [28,29,23,14,30]. However, ordinary supernova remnants are not able to accelerate CRs up to this energy, so a lot of speculations have recently been made, including supermassive black hole activities [14], galaxy mergers [31], super bubbles, interaction-powered supernovae [32], hypernovae [33,34,23,35], transrelativistic supernovae and GRBs [36,37,38,39,40]. But it is highly unclear whether different populations lead to a smooth power-law spectrum and why the energy budget of rare transients is almost comparable to that of ordinary supernovae [23].…”
Section: Extragalactic Astrophysical Sources Hadronuclear Production mentioning
confidence: 99%
“…The numerical modeling of the early spectra and light curve of SN 1998bw (Nakamura et al 2001) Figure 5. One can see that as long as E p,max is larger than 10 19 eV, which can be reached in the GRB and hypernova scenarios (Wang et al 2007(Wang et al , 2008, both N CenA and < A > meet the requirements. It has been also shown that the spectrum and composition of UHECRs accelerated in the WR stellar wind or in the hypernova ejecta are compatible with the PAO's observations (Liu & Wang 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Thanks to their high gas densities, f pp can be quite high and the observed neutrino flux level can be well explained as long as CRs can be accelerated above 100 PeV energies [10,21,[26][27][28]. However, ordinary supernova remnants are not able to accelerate CRs up to this energy, so a lot of speculations have recently been made, including super-massive black hole activities [10], galaxy mergers [29], super bubbles, interaction-powered supernovae [30], hypernovae [21,[31][32][33], transrelativistic supernovae and GRBs [34][35][36][37][38]. But it is highly unclear whether different populations lead to a smooth power-law spectrum and why the energy budget of rare transients is almost comparable to that of ordinary supernovae [21].…”
Section: Hadronuclear Production In Cosmic-ray Reservoirsmentioning
confidence: 99%